FDG-PET predicted unfavorable tumor histology in living donor liver transplant recipients; a retrospective cohort study. (September 2019) - Ling, Louis Leong-Liung; Hsu, Chien-Chin; Yong, Chee-Chien; Elsarawy, Ahmed M.; Chan, Yi-Chia; Wang, Chih-Chi; Li, Wei-Feng; Lin, Ting-Lung; Kuo, Fang-Ying; Cheng, Yu-Fan; Lin, Li-Man; Chen, Chao-Long; et al.
Abstract: Background: Tumor histology affects outcome after liver transplantation (LT) for hepatocellular carcinoma (HCC). This study explores the association between F-18 fluorodeoxyglucose positron emission tomography (FDG-PET) and tumor histology in living donor liver transplantation (LDLT) recipients and their outcome. Materials and methods: Two hundred fifty-eight patients with primary liver tumors who underwent FDG-PET before LDLT were enrolled in this retrospective study. Unfavorable tumor histology was defined as primary liver tumor other than a well- or moderately differentiated HCC. Thirteen patients had unfavorable tumor histology, including 2 poorly differentiated HCC, 2 sarcomatoid HCC, 5 combined hepatocellular cholangiocarcinoma, 3 intrahepatic cholangiocarcinoma, and 1 hilar cholangiocarcinoma. Results: FDG-PET positivity was significantly associated with unfavorable tumor histology ( P < 0.001). Both FDG-PET positivity and unfavorable tumor histology were significant independent predictors of tumor recurrence and overall survival. In a subgroup analysis of patients with FDG-PET-positive tumors, unfavorable tumor histology was a significant independent predictor of tumor recurrence and overall survival. High FDG uptake (tumor to non-tumor uptake ratio ≥ 2) was a significant predictor of unfavorable tumor histology. Patients with high FDG uptake and/or unfavorable tumors had significantly higher 3-year cumulative recurrence rate (70.8% versus 26.2%, P = 0.004) and worse 3-year overall survival (34.1% versus 70.8%, P = 0.012) compared to those with low FDG uptake favorable tumors. Conclusions: The expression of FDG-PET is highly associated with histology of explanted HCC and predicts the recurrence. FDG-PET-positive tumors with high FDG uptake may be considered contraindication for LDLT due to high recurrence rate except when pathology proves favorable histology. Highlights: Unfavorable tumor histology tends to be FDG-PET-positive with high uptake. FDG-PET-negative tumor is suitable for LDLT without awareness of tumor histology. FDG-PET-positive low uptake tumor should be biopsied to determine tumor histology. FDG-PET-positive high uptake tumor should be excluded from LDLT.